2016
DOI: 10.1074/mcp.m115.057505
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the O-Mannose Glycoproteome in Saccharomyces cerevisiae

Abstract: O-Mannosylation is a vital protein modification conserved from fungi to humans. Yeast is a perfect model to study this post-translational modification, because in contrast to mammals O-mannosylation is the only type of O-glycosylation. In an essential step toward the full understanding of protein O-mannosylation we mapped the O-mannose glycoproteome in baker's yeast. Taking advantage of an O-glycan elongation deficient yeast strain to simplify sample complexity, we identified over 500 O-glycoproteins from all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
67
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 63 publications
(108 reference statements)
0
67
0
Order By: Relevance
“…The nucleocytoplasmic O-mannosylation system is only found in yeast and is predicted to serve similar functions as the nucleocytoplasmic O-GlcNAcylation found in all eukaryotic cells except yeast (22). The ER-located PMTs in yeast have wide glycosylation functions of ER/Golgi, cell wall, and secreted proteins, similar to the metazoan GalNAc-type O-glycosylation (23), and in fact it appears that the two types of glycosylation have great overlaps in proteins and glycosites as well as biological functions (20,24). Interestingly, the orthologous metazoans POMT1 and POMT2 are predicted to have narrower substrate specificities and only serve in glycosylating a limited number of proteins, including ␣-DG and cdhs/pcdhs (13,15,19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The nucleocytoplasmic O-mannosylation system is only found in yeast and is predicted to serve similar functions as the nucleocytoplasmic O-GlcNAcylation found in all eukaryotic cells except yeast (22). The ER-located PMTs in yeast have wide glycosylation functions of ER/Golgi, cell wall, and secreted proteins, similar to the metazoan GalNAc-type O-glycosylation (23), and in fact it appears that the two types of glycosylation have great overlaps in proteins and glycosites as well as biological functions (20,24). Interestingly, the orthologous metazoans POMT1 and POMT2 are predicted to have narrower substrate specificities and only serve in glycosylating a limited number of proteins, including ␣-DG and cdhs/pcdhs (13,15,19).…”
mentioning
confidence: 99%
“…This categorization is based on sequence similarities, but a recent study confirmed the func-tional similarity between the human POMT1 and yeast PMT4 enzymes (19). O-Mannosylation of proteins in yeast is widespread, and we recently characterized the yeast O-Man glycoproteome identifying almost 300 glycoproteins that enter the secretory pathway (20). In addition, we also found that yeast has an additional and unique nucleocytoplasmic O-Man glycoproteome, which is predicted to be glycosylated by a yet unknown cytosolic/nuclear O-mannosyltransferase(s) different from the ER-located PMTs (21).…”
mentioning
confidence: 99%
“…Interestingly, Ykl077w‐N′ runs at a much higher molecular weight than would be predicted by its length, suggesting that it is highly glycosylated (Figure B). In support of this, many sites on Ykl077w‐N′ were recently shown to be O ‐mannosylated in a high throughput analysis of glycosylation in yeast (Figure S2). We performed pull downs of Ykl077w‐N′ and Ykl077w‐C′, which demonstrated physical interactions with most of the Golgi glycosylation machinery (Tables S5 and S6).…”
Section: Resultsmentioning
confidence: 81%
“…The mannosylated peptide identified in mouse Pdia3, includes a conserved ProThr-motif that has been demonstrated to carry an O-linked mannose in PDIA3 from human breast cancer cells [31] (S10 Fig). Most interestingly, we very recently found O-mannosyl glycans also in the ER-luminal PDIs and PDI-like proteins from baker´s yeast and found that modification by O-mannosylation occurred in a conserved residue in the proximity of the catalytic CysXXCys motifs [57]. …”
Section: Discussionmentioning
confidence: 99%